Polycystic ovary syndrome and postpartum depression among Hispanics and non-Hispanics: a population-based studyAJOG Global Reports at a Glance - Adriele D. Fugal, MSPH; Joseph B. Stanford, MD, MSPH; Erica B. Johnstone, MD, MHS; Kebba Kah, MPH; Karen C. Schliep, PhD, MSPH (AJOG Global Reports, 2022)
BACKGROUND: Women with polycystic ovary syndrome experience increased health complications during and after pregnancy, including a higher prevalence of postpartum depression. Although previous research has found that Hispanic women with polycystic ovary syndrome experience heightened hyperandrogenism and metabolic effects compared with non-Hispanic women, it is unknown whether they experience other polycystic ovary syndrome–related comorbidities, such as postpartum depression, to a greater degree than their non-Hispanic counterparts. OBJECTIVE: This study aimed to determine the associations among a self-reported prepregnancy diagnosis of polycystic ovary syndrome, polycystic ovary syndrome symptoms (irregular menstruation, hirsutism, and acne), and postpartum depression among a national sample of at-risk women and evaluated the potential effect modification by Hispanic ethnicity. STUDY DESIGN: The study population included 52,267 postpartum (2–6 months) women who completed the US Pregnancy Risk Assessment Monitoring System Phase 8 questionnaire (2016–2018). Data from US states that captured self-reported polycystic ovary syndrome symptoms in the 3 months before pregnancy (n=17 states) were used. Moreover, we performed a subanalysis restricted to data from the Utah Pregnancy Risk Assessment Monitoring System Phase 8 questionnaire (2016–2019; n=5814), as it was the only state that considered self-reported polycystic ovary syndrome symptoms during this period. Postpartum depressed mood and anhedonia, the postpartum depression outcome measurements, were assessed via the following questions, respectively: (1) “Since your new baby was born, how often have you felt down, depressed, or hopeless?” and (2) “Since your new baby was born, how often have you had little interest or little pleasure in doing things you usually enjoyed?” In addition, postpartum depressed mood and anhedonia were assessed separately and as a combined variable. Here, weighted adjusted prevalence ratios and 95% confidence intervals were used to assess the association between polycystic ovary syndrome and postpartum depressed mood and anhedonia among Hispanic women and non-Hispanic women while taking into account preconception sociodemographics, lifestyle, and health history confounding factors. RESULTS: The national study population was composed of 16.8% of Hispanic ethnicity, with 11.4% Hispanic women and 17.1% non-Hispanic women reporting prepregnancy polycystic ovary syndrome symptoms. The study found no association between women reporting prepregnancy polycystic ovary syndrome vs women without polycystic ovary syndrome and the prevalence of postpartum depressed mood and/or anhedonia. Moreover, the results were null when we stratified by Hispanic ethnicity. The Utah study population was composed of 15.5% of women of Hispanic ethnicity, with 5.8% of Hispanic women and 7.4% of non-Hispanic women reporting prepregnancy polycystic ovary syndrome. Symptom-based polycystic ovary syndrome (having irregular menstruation with hirsutism or irregular menstruation with acne), compared with having regular menstruation in the Utah sample, was associated with a 1.54 higher adjusted prevalence ratio (95% confidence interval, 1.14–2.09) for postpartum depressed mood and anhedonia. Stratified analyses by ethnicity indicated a 2- to 5-fold higher prevalence of postpartum depression with symptom-based polycystic ovary syndrome for Hispanic women and a 1.5-fold higher prevalence for non-Hispanic women. CONCLUSION: In this US population-based study, a self-reported prepregnancy diagnosis of polycystic ovary syndrome was not associated with postpartum depression. However, self-reported polycystic ovary syndrome symptoms, including irregular menstruation and acne and/or hirsutism, were associated with a higher probability of postpartum depression, most prominently for Hispanic women. Our findings suggested that capturing polycystic ovary syndrome symptoms among at-risk women may be important for identifying associations with postpartum depression and potentially other comorbidities.